The Repertory Grid in Career Counselling: Method and Information Yield - Cochran, Larry R. (Canadian Journal of Counselling and Psychotherapy, 2012)
George Kelly's (1955) repertory grid technique provides a method for exploring how people make sense of career alternatives and establish individual bases for making decisions. The basic method is explained and seven different types of information that a grid supplies are discussed.